1988
DOI: 10.1177/003693308803300514
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Bilateral Fractures of the Femoral Neck

Abstract: An 80-year-old woman suffered bilateral simultaneous fractures of her hips. This is the first reported case in the elderly. Both hips were replaced by Thompson hemi-arthroplasties at the same operation, and the patient was discharged home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…It is important to note that this patient gave a definite history of a fall which led to the injury in contrast to fatigue fractures [5] where patients describe their leg giving way followed by pain. Bilateral fractured NOF have been reported in the literature in the elderly following minimal trauma [10]. However, in this case described the patient had a background of corticosteroid induced osteoporosis, gross obesity and rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 91%
“…It is important to note that this patient gave a definite history of a fall which led to the injury in contrast to fatigue fractures [5] where patients describe their leg giving way followed by pain. Bilateral fractured NOF have been reported in the literature in the elderly following minimal trauma [10]. However, in this case described the patient had a background of corticosteroid induced osteoporosis, gross obesity and rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 91%
“…Atkinson et al 9 also has reported four cases of bilateral fracture neck femur following violent trauma, one after vehicular accident, two after fall of heavy object and one due to fall from height. There have been few reports of bilateral fracture neck femur in elderly patients following minimal trauma 10 . Also, it is important to have radiographs of pelvis with both hip in initial assessment for every patient, especially for elderly patients and patients with co-morbid conditions to rule out this rare entity.…”
Section: Discussionmentioning
confidence: 99%
“…One case reported by Tair 4 described the injury in detail, but little was included on the specific management plan or guidance for clinicians in the future.…”
Section: Discussionmentioning
confidence: 99%